ANALYSING SCHOENBERG’S PIANO PIECES OP. 19: HISTORY AND METHODOLOGY - EYBL, Martin (Studia Universitatis Babes-Bolyai Musica, 2025)
Schoenberg’s Op. 19 has become a classic in musical analysis. There are hardly any analytical approaches to twentieth-century music that have not been demonstrated using this cycle. Consequently, the body of research on Op. 19 also provides a good overview of analytical methods that were developed for, or have at least been applied to, atonal music.